EFFECTS OF CHEMICAL WEATHERING ON INFRARED SPECTRA OF COLUMBIA RIVER BASALT AND SPECTRAL INTERPRETATIONS OF MARTIAN ALTERATION - Michalski J.R.; Kraft M.D.; Sharp T.G.; Christensen P.R. (My University, 2006)
We investigated the mineralogy of basalt weathering rinds and fresh basaltic rocks using visible/near-infrared (VNIR) (λ = 0.4-2.5 μm) and thermal emission (λ = 6-30 μm) spectroscopy to 1) constrain the effects of chemical weathering on rock spectra, and 2) further understand the context of infrared spectra of Mars, which may contain evidence for weathered rocks and particulates derived from them. VNIR spectra of weathered rock surfaces are generally redder and brighter than fresh surfaces. Thermal infrared spectra of weathered basalts show evidence for aluminous opal and clay minerals (or clay precursor mineraloids) in natural surfaces. Supporting VNIR observations generally do not show the same evidence for neoformed clays or silica because of their textural occurrence as thin coatings and microfracture-fill, and possibly due to poor crystallinity of the aluminosilicate weathering products in this context. Spectral trends observed at Mars, such as the detection of low to moderate (10-25%) abundances of silica and clay that are observed in the thermal infrared but not in the VNIR, are therefore consistent with trends observed for natural rock surfaces in the laboratory. The combined use of thermal infrared and VNIR suggest that vast areas of martian dark regions contain sandy-rocky basaltic materials with weathering rinds and thin coatings that could have formed in conditions of relatively low water/rock ratios. © 2006 Elsevier B.V. All rights reserved.
Keywords: ALTERATION; MARS; MINERALOGY; SPECTROSCOPY; WEATHERING